Morphogenetic Responses of Triticum aestivum L. Calus Culture During Long-Term Effect of Low Positive Temperatures - Avksentieva, Olha; Zhmurko, Vasyl; Chumakova, Viktoriia (Problems of Cryobiology and Cryomedicine, 2022)
The paper presents the findings on the impact of cold exposure at 4°C on chlorophylogenesis, hemogenesis and rhizogenesis in callus culture of winter wheat cultivars. The patterns of morphogenesis in the soft winter wheat in vitro culture during exposure to positive low temperature of various durations (15, 30 and 45 days) have been established. The callus culture of 2–3 passages of cv. Doridna, Statna and Astet was used. The results of experiments showed the preliminary vernalization of calluses for 30 and 45 days to strongly stimulate the chlorophylogenesis and hemogenesis, thereby increasing the frequency of obtaining the regenerant plants during further cultivation. The efficiency of these processes depended on the original cultivar genotype and cold treatment duration. The vernalization, associated with the VRN genes expression, manifested in morphogenesis change, was assumed to occur in the soft winter wheat in vitro culture. Probl Cryobiol Cryomed 2022; 32(3): 214–225